ANALISA KOMPOSISI MINERAL CLAY TERHADAP KUALITAS RESERVOIR BATUPASIR LAPANGAN BETUNG, FORMASI AIRBENAKAT, SUB-CEKUNGAN JAMBI, CEKUNGAN SUMATERA SELATAN - Irmaya, Aisyah Indah; Rahmad, Basuki; Kristanto, Dedy; Buntoro, Aris; Siregar, Anggi Deliana (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2023)
Cumulative fluid production during 2009 - 2021 in the Betung Field, which is the research location and is located in the Jambi sub-basin-South Sumatra Basin (Barber et al., 2005), amounted to 277,923.52 MBbl. The relationship between porosity and permeability can be said in general that if the porosity is greater, the permeability will be greater, but in reality it will be found that certain layers will have large porosity but small permeability, such as in layers containing clay or shale. Mineralogical composition plays an important role, especially with regard to clays, involving several compositions including illite, smectite, kaolinite and chlorite. The presence of quartz and feldspar increases permeability, while clay minerals and calcite tend to have the opposite effect (Jose M. Carcione et al., 2019). The analysis carried out included XRD analysis to determine the mineral composition of the reservoir sandstone of the Airbenakat formation, rock quality analysis (porosity and permeability), well log analysis and then the overall analysis results were linked to production data. Based on XRD analysis, petrophysical analysis of wells 209 and 217 in the Betung field, Airbenakat formation, Jambi sub-basin, South Sumatra basin, the results of XRD and petrophysical analysis show the presence of clay content consisting of Kaolinite, Illite, Smectite and Chlorite which has an influence on reservoir quality, especially permeability, where the greater the clay content, the more obstructed fluid flow is.